The Influence of Group Roles in the Utilization of Tofu Pulp in KWT Lestari Maju Selopamioro Village, Kapanewon Imogiri, Bantul Regency - Maryati, Sri; Puspitojati, Endah; Sukadi, Sukadi (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
This study aimed to analyze the influence of the role of the Women Farmers Group (KWT) in the use of tofu pulp in KWT Lestari Maju, Selopamioro Village, Kapanewon Imogiri, Bantul Regency. The method used was a descriptive quantitative approach with multiple linear regression analysis techniques. The research sample of 32 people was selected by purposive sampling. The independent variables studied included the role of groups as learning classes, cooperation vehicles, and production units, while the dependent variable was the use of tofu pulps. The results showed that the role of groups as a learning class (56.07%), a vehicle for cooperation (57.18%), and a production unit (67.10%) was in the medium category. KWT Lestari Maju classified the utilization of tofu pulps as a medium category, with an average utilization of 41.33%. The regression analysis indicated that the simultaneous variables of learning classes, cooperation vehicles, and production units significantly affect the utilization of tofu pulps (Simultaneous value F 7.513 Sig 0.001 and determination R2 0.387 Sig < 0.05). However, partially, the role as a learning class of Sig 0.008 and production unit of Sig 0.027 has a significant influence, while the cooperation vehicle is not significant Sig 0.348. This indicates that the role of groups was significant in increasing the use of tofu pulp waste into products with selling value, such as crackers. However, there is still a need to strengthen cooperation and continuous further training. Contribution to the Sustainable Development Goals (SDGs): SDG 2: Zero HungerSDG 3: Good Health and Well-beingSDG 15: Life on Land